On the blind spot: ethical conflicts of health care professionals in addressing opioid diversion - a template study protocol for multinational qualitative research - Annette Binder; Sonja Mathes (BMC Medical Ethics, 2026)
Abstract Background Opioid diversion—the unauthorized redirection of prescription opioids—is a growing global concern with significant public health implications. While diversion can occur at many points in the supply chain, instances involving healthcare professionals (HCPs) are particularly complex, as they often occur within clinical settings and most often involve self-medication, substance use disorders among healthcare professionals, or peer dynamics. These cases raise not only legal and professional concerns but also profound ethical dilemmas. To date, the ethical perspectives of HCPs in relation to opioid diversion have been underexplored. This multinational qualitative study aims to investigate how HCPs experience and navigate ethical conflicts related to opioid diversion in clinical contexts. The study focuses on the lived experiences and moral reasoning of HCPs who encounter diversion, either among colleagues or in relation to their own practice. It seeks to explore and identify barriers to seeking help and accessing harm reduction, and to understand how these challenges vary across different healthcare systems. Methods Semi-structured interviews will be conducted with HCPs working in clinical settings where opioids are used. A fictional scenario involving suspected diversion among peers will be used to encourage reflective discussion. This approach is intended to minimize social desirability bias and potential legal concerns in comparison to assessing experienced diversion. The interview guide is structured around the five steps of ethical analysis as outlined by Marckmann, supporting a theory-informed exploration of individual and systemic dilemmas. Data will be analyzed using reflexive thematic analysis (RTA), allowing for nuanced insights into both explicit reasoning and latent moral constructs. Recruitment of HCPs takes place in hospital departments characterized by frequent opioid use. The study protocol is intended for international implementation to support cross-national comparative analysis. Discussion This study will generate a deeper understanding of the ethical tensions HCPs face in the context of opioid diversion. By identifying structural and cultural drivers behind moral distress, the findings may help address stigma and inform the development of ethically guided harm reduction strategies as well as supportive structures for HCPs. The cross-national comparative perspective aims to contribute to an international framework for reducing opioid-related harm in healthcare.